(untitled) (Fiep Bulletin - online, 2014)
Motor performance is one of the goal categories of physical education lessons on primary and secondary schools in Slovakia. Motor performance in schools is evaluated on the basis of achieved results in motor tests. In the past there used to be published more works about this problem (Moravec-Havlíèek-Zapletalová 1990, Moravec-Sedláèek-Kampmiller 1996, Antala et al., 1997, Antala 2002, Filho 2003 etc.). There is used simplified battery of EUROFIT test - standing broad jump, 1 min sit-ups, shuttle run 4 x 10 m, 12 minutes endurance run or alternatively endurance shuttle run in gymnasium. By this test battery are tested pupils from 10 to 18 years in primary and secondary schools. Testing is performed once a school year, mostly at the end of school year (April, May or June). Because of performance in motor tests depends from physical dispositions, there are disadvantaged individuals, who have not these assumptions. In order to equalize motor performance evaluation, there is need to look for possibilities of performance estimation in each motor test on the basis of physical dispositions, concretely on the basis of body height and body weight.